Cross‐Linked Polyphosphazene Hollow Nanosphere‐Derived N/P‐Doped Porous Carbon with Single Nonprecious Metal Atoms for the Oxygen Reduction Reaction. Issue 34 (1st July 2020) - Wei, Xuan; Zheng, Diao; Zhao, Ming; Chen, Hongzhong; Fan, Xun; Gao, Bin; Gu, Long; Guo, Yi; Qin, Jianbin; Wei, Jing; Zhao, Yanli; Zhang, Guangcheng
Abstract: Heteroatom‐doped polymers or carbon nanospheres have attracted broad research interest. However, rational synthesis of these nanospheres with controllable properties is still a great challenge. Herein, we develop a template‐free approach to construct cross‐linked polyphosphazene nanospheres with tunable hollow structures. As comonomers, hexachlorocyclotriphosphazene provides N and P atoms, tannic acid can coordinate with metal ions, and the replaceable third comonomer can endow the materials with various properties. After carbonization, N/P‐doped mesoporous carbon nanospheres were obtained with small particle size (≈50 nm) and high surface area (411.60 m 2 g −1 ). Structural characterization confirmed uniform dispersion of the single atom transition metal sites (i.e., Co‐N2 P2 ) with N and P dual coordination. Electrochemical measurements and theoretical simulations revealed the oxygen reduction reaction performance. This work provides a solution for fabricating diverse heteroatom‐containing polymer nanospheres and their derived single metal atom doped carbon catalysts. Abstract : A facile template‐free method is developed for the synthesis of functional cross‐linked polyphosphazene nanospheres with tunable hollow structures and properties. After coordinating with metal ions, these nanospheres are directly pyrolyzed to afford mesoporous hollow carbon nanospheres with single atom Co‐N2 P2 sites for superior electrocatalysis.